Lipolysis-derived fatty acids are needed for homeostatic control of sterol element-binding protein-1c driven hepatic lipogenesis - Paola Peña de la Sancha; Beatrix Irene Wieser; Silvia Schauer; Helga Reicher; Wolfgang Sattler; Rolf Breinbauer; Martina Schweiger; Margarete Lechleitner; Saša Frank; Rudolf Zechner; Dagmar Kratky; Peter John Espenshade; et al. (Communications Biology)
Abstract Sterol Regulatory Element-Binding Protein-1c (SREBP-1c) is translated as an inactive precursor (P-SREBP-1c) postprandially. Low levels of unsaturated fatty acids (uFAs) and high insulin promote its proteolytic activation, yielding N-SREBP-1c that drives fatty acid (FA) biosynthesis. During fasting, however, lipogenesis is low, and adipose tissue lipolysis supplies the organism with FAs. Adipose Triglyceride Lipase (ATGL) is the rate-limiting enzyme for adipose tissue lipolysis, and it preferentially releases uFAs. Therefore, we hypothesized that adipose ATGL-derived uFAs suppress P-SREBP-1c activation in the liver. In this study, we show that (I) N-SREBP-1c is transiently higher in livers of fasted and refed adipose specific Atgl knockout mice than in control livers. (II) This effect is reversed by injection of uFAs. (III) uFAs inhibit endoplasmic reticulum to Golgi-apparatus transport of SREBP Cleavage-Activating Protein (SCAP) in hepatocytes, which is essential for SREBP activation. Our findings demonstrate that adipose tissue ATGL derived uFAs attenuate P-SREBP-1c activation in the liver mainly after refeeding. We propose that this ATGL/SREBP-1c axis adds an additional layer of coordination between lipogenesis and lipolysis.